2015
DOI: 10.1159/000430140
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid-Induced Cardiac Differentiation of Murine Pluripotent Stem Cells: Transcriptional Profiling and Effect of a Small Molecule Synergist of Wnt/β-Catenin Signaling Pathway

Abstract: Background: Reproducible and efficient differentiation of pluripotent stem cells (PSCs) to cardiomyocytes (CMs) is essential for their use in regenerative medicine, drug testing and disease modeling. The aim of this study was to evaluate the effect of some previously reported cardiogenic substances on cardiac differentiation of mouse PSCs. Methods: Differentiation was performed by embryoid body (EB)-based method using three different murine PSC lines. The differentiation efficiency was monitored by RT-qPCR, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…Hence, the findings of this study support the hypothesis that iPS-derived cardiac myocytes can provide an adequate model for pharmacological and toxicological studies. New strategies for the differentiation of stem cells promise to improve the functional consistency of hiPS-derived cardiomyocytes [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the findings of this study support the hypothesis that iPS-derived cardiac myocytes can provide an adequate model for pharmacological and toxicological studies. New strategies for the differentiation of stem cells promise to improve the functional consistency of hiPS-derived cardiomyocytes [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation and purification of murine induced pluripotent stem cell-derived cardiomyocytes (iPSCM) is described elsewhere 16 . iPSCM at day 16 of differentiation were cultured on a 120-electrode microarray.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in diabetic rats, vitamin C decreased lipid peroxidation and increased the activities of antioxidant enzymes in the kidneys of diabetic rats, as well as reduced urinary albumin excretion (UAE), decreased kidney weight, and glomerular basement membrane (GBM) thickness [19]. It was reported that vitamin C protects kidney function and renal arterial reactivity against renal ischemic injury in mice [20] and vitamin C can induce cardiomyocytes differentiation of murine pluripotent stem cells through the synergistic effect of Wnt-signaling pathway [21]. Vitamin C has also been proven to function in vitamin E recycling and protect renal cells from apoptosis and senescence, increased regenerative ability of cells and fibrosis [22].…”
Section: Discussionmentioning
confidence: 99%